Role of point defects in hybrid phase TiO2 for resistive random-access memory (RRAM). (24th April 2019) - Irshad, Muhammad Sultan; Abbas, Adil; Qazi, Hummad Habib; Aziz, M Hammad; Shah, Matiullah; Ahmed, Ashfaq; Idrees, M
Abstract: TiO2 thin films based resistive random-access memory was examined for resistive switching behavior. TiO2 thin films were deposited on FTO glass substrate using single step hydro-thermal method with different synthesis parameters. The x-ray Diffraction results confirmed the existence of both anatase and rutile phases (hybrid) in one film and only rutile phase in other film. Morphological studies of prepared TiO2 thin film were carried out using scanning electron microscope. The photo-luminescence results revealed the presence of Ti interstitial defects (Ti +4 & Ti +3 ) and oxygen vacancies in hybrid phase film. Whereas, Ti interstitial defects were absent in rutile phase film. Current voltage characteristics showed the presence of resistive switching in the hybrid phase film only. The switching characteristics have been attributed to originate from the presence of Ti interstitial defects, facilitating Ag + ion migration in TiO2 dielectric layer. The observed resistive switching has been explained on the electrochemical metallization (ECM) model.